Synthesis and evaluation of hedgehog signaling inhibitor with novel core system. Issue 15 (1st August 2015) - Ohashi, Tomohiro; Tanaka, Yuta; Shiokawa, Zenyu; Banno, Hiroshi; Tanaka, Toshio; Shibata, Sachio; Satoh, Yoshihiko; Yamakawa, Hiroko; Yamamoto, Yukiko; Hattori, Harumi; Kondo, Shigeru; Miyamoto, Maki; et al.
Graphical abstract: Abstract: As we previously reported, N -methylpyrrolo[3, 2- c ]pyridine derivatives 1 (TAK-441) was discovered as a clinical candidate of hedgehog (Hh) signaling inhibitor by modification of the upper part. We next focused on modification of the lower part including core skeletons to discover new Hh signaling inhibitors with novel core rings. Efforts to find novel chemotypes by using X-ray single crystal structure analysis led to some potent Hh signaling inhibitors (2c, 2d, 2e, 2f ) with novel core ring systems, which had benzamide moiety at the 5-position as a key component for potent activity. The suppression of Gli1 expression with these new Hh signaling inhibitors were weaker than that of compound 1 (TAK-441) because of low pharmacokinetic property. We recognized again TAK-441 is a good compound as clinical candidate with good structural and pharmacokinetic advantages.